Prototype Design of a Fishing Boat Safety Monitoring System Using LoRa and Microsensor Devices - Sugiarto, Eka; Suhendi, Asep; Abdussalam, M. Yusup; Husniah, Zahira Aulia; Lestari, Annisa Puji (Universitas Telkom, 2023)
This paper reports a prototype of a low-cost tracking and monitoring system to address the challenges faced by Indonesian fishermen. The lack of safety equipment in their boats exposes them to high risks of work-related accidents and illnesses. Data from the National Basarnas Center reveals a staggering 24,000 annual fatalities among fishermen during their activities. These issues stem from a combination of factors: poorly designed boats, low prioritization of safety, and the lack of readily available preventive measures. Moreover, the development of telecommunications infrastructure in aquatic areas presents its unique obstacles. In response, this study proposes a prototype design for a